2015
DOI: 10.1111/faam.12047
|View full text |Cite
|
Sign up to set email alerts
|

Framing Performance Management of Acute‐Care Hospitals by Interlacing NPM and Institutional Perspectives: A New Theoretical Framework

Abstract: This paper develops a theoretical framework which combines ideas underlying new public management (NPM) with new institutional sociology (NIS) to explore the development of performance management during a period of healthcare reform. The framework distinguishes three categories of explanatory variables; NPM antecedents, the institutional environment and institutional elements within a three tier level of analysis; economic/political, organisational field and organisational unit level. Evidence to support the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 37 publications
0
28
0
3
Order By: Relevance
“…Although multi-level analyses, such as that outlined above, are beginning to gain prominence in institutional research (Dillard et al 2004, Hopper and Major 2007, Purdy and Gray 2009, Smets et al 2012, Moore 2013, Bitektine and Haack 2015, they are still relatively rare in the PMM literature. Insofar as researchers have considered how PMM practices evolve across different levels of institutional fields, they have mainly explored the development of fieldlevel practices and how individual organisations adapt such practices (Modell et al 2007, Conrad and Uslu, 2012, Boitier and Riviere 2013, Kelly et al 2015. By contrast, by drawing attention to the recursive relationships between these levels of analysis, the framework advanced in this paper invites research into how individual organisations influence field-level practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multi-level analyses, such as that outlined above, are beginning to gain prominence in institutional research (Dillard et al 2004, Hopper and Major 2007, Purdy and Gray 2009, Smets et al 2012, Moore 2013, Bitektine and Haack 2015, they are still relatively rare in the PMM literature. Insofar as researchers have considered how PMM practices evolve across different levels of institutional fields, they have mainly explored the development of fieldlevel practices and how individual organisations adapt such practices (Modell et al 2007, Conrad and Uslu, 2012, Boitier and Riviere 2013, Kelly et al 2015. By contrast, by drawing attention to the recursive relationships between these levels of analysis, the framework advanced in this paper invites research into how individual organisations influence field-level practices.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that institutional complexity, originating in heterogeneous and competing constituency demands, can be a source of contradictory PMM practices is well-documented in prior research. Building on the more general insight that such complexity often creates contradictions and tensions in organisations (Meyer and Rowan 1977, Powell 1988, Seo and Creed 2002, Brignall and Modell (2000) including public health care (Modell 2001, Chang, 2006, Østergren 2006, Conrad and Uslu, 2012, Kelly et al 2015, higher education (Modell 2003, 2005, Boitier and Riviere 2013, central government (Modell et al 2007, Modell andWiesel 2008) and state-owned enterprises (Siti-Nabiha and Scapens 2005, Sharma et al 2010, Sundin et al 2010.…”
Section: The Impact Of Institutional Complexity On Organisational Pmmmentioning
confidence: 99%
“…This point has been reaffirmed in later studies (Doolin, 2002;Hartley & Kautsch, 2014;Kitchener, 2000;Waring & Currie, 2009), and there is evidence of greater participation of clinicians in management globally together with cognizance of their increased accountability (Fulop & Day, 2010;Kelly, Doyle, & O'Donohoe, 2015;Wikström & Dellve, 2009). Early research on public sector organizations such as hospitals has concluded that there can exist a decoupling of service delivery by professionals such as doctors and managerial activity (Meyer & Scott, 1992;Scott & Meyer, 1994).…”
Section: Coordination In Professional Organizationsmentioning
confidence: 94%
“…This is the context which we use to illustrate the challenges confronting performance management in public services. It is interesting to note that a number of complexity theory advocates have identified health care as a suitable context for study (Arndt and Bigelow, ; Geyer and Rihani, ; and Rhodes et al., ) and performance management in health care is as complex and elusive as ever (Chang, ; and Kelly et al., ).…”
Section: Performance Management In a Complex Settingmentioning
confidence: 99%